Pengaruh Penerapan Manajemen Pemasaran Jasa Pendidikan terhadap Daya Saing Antar Sekolah di MTs Negeri 2 Rejang Lebong - Aglesia, Ade Sonnie; Idi Warsah; Jumirah Warlizasusi (Education Management: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze the impact of implementing educational service marketing management on the competitiveness of MTs Negeri 2 Rejang Lebong amidst competition with other educational institutions. The research method employed is descriptive qualitative, utilizing data collection techniques such as in-depth interviews, observation, and documentation. The findings indicate that the traditional marketing strategies implemented, such as promotion through print media, drumband parades, and door-to-door visits, have not been sufficiently effective in increasing the number of new applicants. Digital marketing through platforms like Instagram and Facebook has been initiated, but its management remains suboptimal. Internal factors, such as limited educational facilities and teacher competency, as well as external factors, including the presence of other educational institutions with student shuttle programs and strengths in religious-based education, also influence the school's competitiveness. This study recommends the integration of better-managed digital marketing strategies and improvements in the quality of educational services to strengthen the school's competitiveness.